2002
DOI: 10.1152/jn.2002.88.2.1073
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Impairs Long-Term Potentiation in Rat Hippocampal Slices

Abstract: To determine if 12-h sleep deprivation disrupts neural plasticity, we compared long-term potentiation (LTP) in five sleep-deprived and five control rats. Thirty minutes after tetanus population spike amplitude increased 101 +/- 15% in 16 slices from sleep deprived rats and 139 +/- 14% in 14 slices from control rats. This significant (P < 0.05) reduction of LTP, the first demonstration that the sleep deprivation protocol impairs plasticity in adult rats, may be due to several factors. Reduced LTP may indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 24 publications
11
110
2
Order By: Relevance
“…Extended periods of sleep deprivation for 24-72 h appear to eliminate or reduce LTP induction in vitro (Campbell et al 2002;McDermott et al 2003). However, brief periods of sleep deprivation only appear to disrupt signaling underlying LTP maintenance while induction remains intact (Vecsey et al 2009;Florian et al 2011).…”
Section: Sleep Deprivation Impairs Hippocampal Synaptic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Extended periods of sleep deprivation for 24-72 h appear to eliminate or reduce LTP induction in vitro (Campbell et al 2002;McDermott et al 2003). However, brief periods of sleep deprivation only appear to disrupt signaling underlying LTP maintenance while induction remains intact (Vecsey et al 2009;Florian et al 2011).…”
Section: Sleep Deprivation Impairs Hippocampal Synaptic Plasticitymentioning
confidence: 99%
“…Long-term potentiation (LTP), a form of synaptic plasticity, is a long-lasting change in the strength of synaptic connections through the involvement of various molecular signaling cascades and, in some cases, protein synthesis (Bliss and Lomo 1973;Whitlock et al 2006). Campbell et al (2002) examined LTP in area CA1 in vitro after 12 h of total sleep deprivation, and found that the procedure inhibited induction of LTP in the hippocampus of rodents. Since this study, follow-up studies have given us an in-depth perspective on the effects of sleep deprivation on LTP.…”
Section: Sleep Deprivation Impairs Hippocampal Synaptic Plasticitymentioning
confidence: 99%
“…42 Handling can also produce unwanted side effects, including increased levels of glucocorticoids or changes in neurotransmitter receptors, that could conceivably mask the expression of memory. 43,44 To rule out potential stress-induced memory deficits caused by the physical handling of the animals during the sleep deprivation procedure, animals were handled with context changes for 9 h during the day similar to the degree of handling in corresponding sleep deprivation experiments, received LFI training at the end of the day at ZT 11 and then tested for LTM 24 h later. Daytime-handled animals demonstrated robust LTM with significantly shorter total response times ( Figure 1B) and mouth times ( Figure S1B) than naĂŻve animals.…”
Section: Sleep Deprivation Blocks the Induction Of Ltmmentioning
confidence: 99%
“…After the third session, the animals were left undisturbed for another 3 to 7 days in the home cages before being killed. This post-REMS deprivation recovery period was employed to differentiate between an immediate negative effect of REMS deprivation on LTP induction (Campbell et al, 2002;Davis et al, 2003;McDermott et al, 2003) and possible longer-term effects on hippocampal maturation. The latter was investigated in this work by testing LTP stability (Kramar and Lynch, 2003).…”
Section: Experimental Time-linementioning
confidence: 99%
“…After this period, we could still induce similar levels of LTP in all treatment groups. Accordingly, it is reasonable to assume that the instability of LTP in the Y-REMSD animals is a longer-term consequence of early REMS deprivation on hippocampal developmental processes and not an immediate, negative and quickly reversible effect on synaptic plasticity, as observed in adult studies (McDermott et al, 2003;Campbell et al, 2002).…”
Section: Effect Of Hpa Axis and Rems Deprivation On Ltp Inductionmentioning
confidence: 99%